Ditelluride-Bridged PEG-PCL Copolymer as Folic Acid-Targeted and Redox-Responsive Nanoparticles for Enhanced Cancer Therapy - Pang, Zekun; Zhou, Jiayan; Sun, Chunyang (Frontiers in Chemistry, 2020)
The development of the nanosized delivery systems with targeting navigation and efficient cargo release for cancer therapy has attracted great attention in recent years. Herein, a folic acid (FA) modified PEGylated polycaprolactone containing ditelluride linkage was synthesized through a facile coupling reaction. The hydrophobic doxorubicin (DOX) can be encapsulated into the polymeric micelles, and such nanoparticles (F-TeNPDOX) exhibited redox-responsive drug release under abundant glutathione (GSH) condition due to the degradation of ditelluride bonds. In addition, flow cytometric analyses showed that the FA ligands on F-TeNPDOX could facilitate their cellular uptake in 4T1 breast cancer cells. Therefore, F-TeNPDOX led to the promoted drug accumulation and enhanced growth inhibition on 4T1 tumor in vivo. The obtained results suggest F-TeNPDOX excellent potential as nanocarriers for anticancer drug delivery.